2000
DOI: 10.1111/1468-0335.00221
|View full text |Cite
|
Sign up to set email alerts
|

Caught in a Trap? Wage Mobility in Great Britain: 1975–1994

Abstract: In this paper I study wage mobility in Great Britain using the New Earnings Surveys of 1975-94 and the British Household Panel Surveys of 1991-94. Measuring mobility in terms of decile transition matrices, I find a considerable degree of immobility within the wage distribution from one year to the next. Mobility is higher when measured over longer time periods. Those in lower deciles in the wage distribution are much more likely to exit into unemployment and non-employment. Measuring mobility by studying chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 11 publications
(3 reference statements)
10
76
3
1
Order By: Relevance
“…Given the evidence of its persistent dynamic nature, it is difficult to rationalize that multiple job-holding is a temporary individual response to financial shocks. Nonetheless, the permanency of moonlighting is consistent with previous findings of the literature that have showed that low-paid workers (who are more likely to engage in multiple job-holding) are typically trapped in a "low-pay/no pay" vicious cycle (Webb et al, 1996;Machin, 1999;Stewart, 1999;Stewart and Swaffield, 1999;Dickens, 2000;TUC, 2007).…”
Section: The Profile Of the Multiple Job-holdersupporting
confidence: 85%
“…Given the evidence of its persistent dynamic nature, it is difficult to rationalize that multiple job-holding is a temporary individual response to financial shocks. Nonetheless, the permanency of moonlighting is consistent with previous findings of the literature that have showed that low-paid workers (who are more likely to engage in multiple job-holding) are typically trapped in a "low-pay/no pay" vicious cycle (Webb et al, 1996;Machin, 1999;Stewart, 1999;Stewart and Swaffield, 1999;Dickens, 2000;TUC, 2007).…”
Section: The Profile Of the Multiple Job-holdersupporting
confidence: 85%
“…The study also includes Germany, but uses the GSOEP for the analysis. The result for the UK is confirmed by Dickens (2000).…”
mentioning
confidence: 58%
“…This allows to investigate whether and how many quintiles individuals have moved between two periods. Since such transition matrix approaches fail to capture the movement within each quintile so that mobility is likely to be underestimated, I additionally make use of the measure by Dickens (2000).…”
Section: Wage Mobility Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…13 For females, the overall pattern of results with respect to the importance of plant size and industrial relations remains unchanged, with employer size (again except for the smallest size class in manufacturing) playing no significant role for low-pay persistence and works councils significantly reducing the probability of staying lowpaid. Compared with the results reported in Table 5, the marginal effect of works councils on low-pay persistence in manufacturing becomes even more pronounced, with a point estimate of -0.27 which is now statistically significant at the 1 per cent level.…”
Section: Robustness Checksmentioning
confidence: 97%